Brainstem Mechanisms of Pain Modulation: A within-Subjects 7T fMRI Study of Placebo Analgesic and Nocebo Hyperalgesic Responses - Crawford, Lewis S.; Mills, Emily P.; Hanson, Theo; Macey, Paul M.; Glarin, Rebecca; Macefield, Vaughan G.; Keay, Kevin A.; Henderson, Luke A. (The Journal of neuroscience, 2021)
Pain perception can be powerfully influenced by an individual's expectations and beliefs. Although the cortical circuitry responsible for pain modulation has been thoroughly investigated, the brainstem pathways involved in the modulatory phenomena of placebo analgesia and nocebo hyperalgesia remain to be directly addressed. This study used ultra-high-field 7 tesla functional MRI (fMRI) to accurately resolve differences in brainstem circuitry present during the generation of placebo analgesia and nocebo hyperalgesia in healthy human participants ( N = 25, 12 male). Over 2 successive days, through blinded application of altered thermal stimuli, participants were deceptively conditioned to believe that two inert creams labeled lidocaine (placebo) and capsaicin (nocebo) were acting to modulate their pain relative to a third Vaseline (control) cream. In a subsequent test phase, fMRI image sets were collected while participants were given identical noxious stimuli to all three cream sites. Pain intensity ratings were collected and placebo and nocebo responses determined. Brainstem-specific fMRI analysis revealed altered activity in key pain modulatory nuclei, including a disparate recruitment of the periaqueductal gray (PAG)–rostral ventromedial medulla (RVM) pathway when both greater placebo and nocebo effects were observed. Additionally, we found that placebo and nocebo responses differentially activated the parabrachial nucleus but overlapped in engagement of the substantia nigra and locus coeruleus. These data reveal that placebo and nocebo effects are generated through differential engagement of the PAG–RVM pathway, which in concert with other brainstem sites likely influences the experience of pain by modulating activity at the level of the dorsal horn. SIGNIFICANCE STATEMENT Understanding endogenous pain modulatory mechanisms would support development of effective clinical treatment strategies for both acute and chronic pain. Specific brainstem nuclei have long been known to play a central role in nociceptive modulation; however, because of the small size and complex organization of the nuclei, previous neuroimaging efforts have been limited in directly identifying how these subcortical networks interact during the development of antinociceptive and pro-nociceptive effects. We used ultra-high-field fMRI to resolve brainstem structures and measure signal change during placebo analgesia and nocebo hyperalgesia. We define overlapping and disparate brainstem circuitry responsible for altering pain perception. These findings extend our understanding of the detailed organization and function of discrete brainstem nuclei involved in pain processing and modulation.